Biosynthesis of ethylene glycol from d-xylose in recombinant Escherichia coli. Issue 1 (1st January 2018) - Wang, Yuhui; Xian, Mo; Feng, Xinjun; Liu, Min; Zhao, Guang
ABSTRACT: Ethylene glycol (EG) is an important chemical used as antifreeze and a raw material in polyester synthesis. The EG biosynthetic pathway from D -xylose with D -xylonate as key intermediate has some advantages, but showed low EG production. Here, we reconstructed and optimized this pathway in Escherichia coli . In view of the greater intracellular prevalence of NADH, an aldehyde reductase FucO using NADH was employed to convert glycoaldehyde into EG, in replacement of NADPH-dependent reductase YqhD. To suppress the accumulation of by-products acetate and glycolate, two genes arcA and aldA were knocked out. The resultant strain Q2843 produced 72 g/L EG under fed-batch fermentation conditions, with the yield of 0.40 g/g D -xylose and EG productivity of 1.38 g/L/h. The use of NADH-dependent enzyme FucO and by-product elimination significantly improved the performance of EG producing strain, which represented the highest titer, yield and productivity of EG reported so far.